HOW AGRICULTURE IS PERCEIVED FROM THE BANKS OPERATING IN ALBANIA - Thomaj, Eneida (European Scientific Journal, ESJ, 2015)
This paper is oriented in trying to analyze the overall opinion or perception that Albanian banks have toward agriculture sector in general, and agriculture lending in particular. To get a full picture of the situation, different statistical parameters regarding banking activity in Albania are presented, such as the banking sector expansion in Albanian territory to understand how rural and urban areas are covered from the banking presence; their electronic products offered to understand the ease of contact from the client with the banks etc. A survey was realized (which included ten of the biggest banks operating in Albania). The survey tries to gain knowledge about the future expectations of the banks as per agriculture lending; their perception as per client orientation behavior; the banks future decision as what share of their portfolio will be dedicated to agriculture etc. The survey gives answers to question like, what part of loan portfolio is dedicated to agriculture and growth expectations in the future; how are loan standards being applied and expectations in the future; main factors affecting loan demand etc. At the end, this paper concluded about the future expectations of loan portfolio structure of banking institutions.